SIMBOL ROKOK DALAM MOUNDA PADA SUKU TOLAKI DI DESA MOKALELEO KECAMATAN PURIALA KABUPATEN KONAWE - Seven Bintang (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
The purpose of this study is to find out and describe the symbolic meaning of cigarettes in Mounda in the Tolakinese. The data obtained were analyzed descriptively qualitatively. Data collection is done through observation techniques involved (participation observation) and in-depth interviews. The results of this study indicate that cigarettes in the mounda tradition have deep symbolic meanings. Mounda is done by using cigarettes and matches placed on a plate and then covered with handkerchiefs brought by the invitees to be presented to the families to be invited. The activity of inviting (mounda) by using cigarettes has the meaning as a form of appreciation and respect for those invited. Thus, relatives or invited people find it hard not to attend the intended invitation. Keywords: cigarette, symbol, mounda, Tolakinese